Assessing the environmental impact of logistics in online and offline B2C purchasing processes in the apparel industry. Issue 1 (2016) - Mangiaracina, Riccardo; Perego, Alessandro; Perotti, Sara; Tumino, Angela
This paper presents an activity-based model for the assessment of the environmental impact of the purchasing process in the apparel industry, comparing traditional in-store and B2C e-commerce channels with a focus on logistics activities. Interviews with company managers and secondary sources were used to develop and validate the model. A base case was selected and a sensitivity analysis was carried out. The impact of logistics is generally very high in both the online and offline purchasing processes (i.e., 99% and 62% of total CO2e emissions respectively). In the online case, the location of the consumer house (i.e., inside or outside the city centre) is the parameter with the greatest environmental impact, whereas in the offline case the distance between the consumer house and the store was the most significant factor. From a managerial viewpoint, the model helps practitioners understand the environmental consequences of their business and supports internal monitoring procedures.